2009
DOI: 10.1002/lary.20684
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence and survival of head and neck adenoid cystic carcinoma after definitive resection

Abstract: Objectives/Hypothesis: To determine factors impacting recurrence and long-term survival of adenoid cystic carcinoma (ACC) of the head and neck after definitive resection.Study Design: Retrospective cohort study at an academic tertiary care hospital.Methods: Patients with ACC of the head and neck treated at our institution were reviewed. Those not receiving surgery, or with metastatic disease were excluded. Clinicopathological data on each patient was collected.Results: Of 113 patients identified with ACC, 99 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
99
8
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 20 publications
(38 reference statements)
11
99
8
4
Order By: Relevance
“…Recent data also suggests intraneural, rather than perineural, invasion has a larger impact on survival in head and neck ACC 41. Other parameters that correlate with local recurrence after surgery are age, nonsalivary or minor salivary gland primary, T classification, tumor grade, lymphovascular invasion, and positive surgical margins 5, 11, 38, 42, 43…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data also suggests intraneural, rather than perineural, invasion has a larger impact on survival in head and neck ACC 41. Other parameters that correlate with local recurrence after surgery are age, nonsalivary or minor salivary gland primary, T classification, tumor grade, lymphovascular invasion, and positive surgical margins 5, 11, 38, 42, 43…”
Section: Introductionmentioning
confidence: 99%
“…Although postoperative radiation seems to improve local control rates, the impact on ACC‐specific survival is not clear 43, 50, 51. Evaluation of survival is confounded by the requirement for long‐term follow‐up as one half of recurrences manifest after 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Adenoid cystic carcinoma (ACC) is an infrequent malignant neoplasm that originates most commonly in the major and minor salivary glands of the head and neck region, and represents approximately 1-2% of all malignant neoplasms of the head and neck. [1][2][3] Sites other than the head and neck region can also be involved, including the breast, prostate and cuticulum. [4][5][6] As an epithelial malignant tumour, ACC is characterized by infiltrative growth and perineural spread, which results in a high rate of recurrence despite aggressive surgical resection.…”
mentioning
confidence: 99%
“…Nascimento et al excluded ACC of the ear canal, lacrimal glands, larynx, esophagus, and trachea from minor salivary ACC, while others included one or more of them in minor salivary ACC. 10,16,11,19 The present authors used the same definition of minor salivary gland ACC as Nascimento et al, 16 and further termed ACC from other secretary glands beyond major or minor salivary glands in the head and neck region as nonsalivary ACC. In this study, minor salivary ACC had inferior prognosis (log-rank test, EFS, P = 0.02; OS, P = 0.014) than major salivary ACC, compatible with that proposed by Nascimento et al.…”
Section: Discussionmentioning
confidence: 95%
“…Khan et al reported that sinonasal ACC had worse outcomes than major salivary gland ACC, and Oplatek et al suggested that major salivary gland ACC had better outcomes than minor salivary gland ACC. 10,16,19 The definition of minor salivary gland ACC is inconsistent. Nascimento et al excluded ACC of the ear canal, lacrimal glands, larynx, esophagus, and trachea from minor salivary ACC, while others included one or more of them in minor salivary ACC.…”
Section: Discussionmentioning
confidence: 99%